Water-based adhesive and lithium battery diaphragm using same
By using epoxy acrylate and boron nitride-silicon polymer composites to prepare coating slurries, the problem of water-based adhesive failure at high temperatures is solved, and the heat resistance and mechanical properties of the lithium battery separator are significantly improved, ensuring that The stability and safety of the battery.
Patent Information
- Application Number
- CN202411227306.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The failure of existing water-based adhesives in high temperature environments leads to insufficient heat resistance and safety of the lithium battery separator, affecting the stability and safety of the battery.
Epoxy acrylate is used as the bonding material, and is prepared by adding polyimide, alumina powder, boron nitride-silicon polymer composite material, dispersant, thickener, and wetting agent, and deionized water is used as solvent. The coating slurry is combined with the pretreatment of boron nitride and the silicon polymer composite to improve the heat resistance of the coating slurry.
The heat resistance and mechanical properties of the lithium battery separator are significantly improved, the needle puncture strength is improved, and the heat shrinkage rate is reduced, ensuring the stability and safety of the lithium battery in high temperature environments.
Smart Images

Figure BDA0005025020930000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to a water-based adhesive and a lithium battery separator using the water-based adhesive. Background Art
[0002] As a key technology for modern energy storage and electric drive, lithium batteries are widely used in consumer electronics, electric vehicles and energy storage systems. The performance and safety of lithium batteries depend largely on their internal structure and materials, and the separator, as a key component inside the battery, is mainly used to isolate the positive and negative electrode materials and prevent short circuits, thereby ensuring the normal operation of the battery. Therefore, in the production of lithium battery separators, the selection of adhesives is crucial to the performance of the separator.
[0003] The adhesive needs to have excellent thermal stability and bonding strength to ensure the stability and safety of the separator in high temperature environments. The water-based adhesive needs to maintain good adhesion under high temperature conditions to prevent melting or falling off, which would cause the separator material to melt, shrink, or lose electrolyte permeability, thus affecting the safety of the battery.
[0004] In order to solve the above problems and improve the heat resistance of lithium battery separators, the present invention provides an aqueous adhesive and a lithium battery separator using the aqueous adhesive. Summary of the invention
[0005] The object of the present invention is to provide an aqueous adhesive and a lithium battery separator using the aqueous adhesive to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A water-based adhesive, the water-based adhesive is epoxy acrylate, and the preparation method of the epoxy acrylate is: take acrylic acid, tetrabutylammonium bromide, and p-hydroxyanisole, stir evenly to obtain a mixture A; take bisphenol A type epoxy resin and tetrabutylammonium bromide, heat to 100°C, stir evenly, add pentaerythritol, condense and reflux for 2-3h, cool to 80-85°C, add the mixture A, react for 3-5h, cool, and obtain epoxy acrylate.
[0008] A coating slurry comprises the following components, measured by weight: 30-35 parts of polyimide, 450-460 parts of aluminum oxide powder, 20-25 parts of boron nitride-silicon polymer composite material, 1000-1050 parts of deionized water, 20-22 parts of dispersant, 2-3 parts of thickener, 2.2-2.5 parts of wetting agent, and 55-60 parts of epoxy acrylate.
[0009] A method for preparing a coating slurry comprises the following steps:
[0010] Step 1: taking modified boron nitride and deionized water, and ultrasonically dispersing them to obtain a modified boron nitride solution; taking silicon polymer and deionized water, and ultrasonically dispersing them to obtain a silicon polymer solution; adding the silicon polymer solution to the modified boron nitride solution, reacting at 60-65° C. for 5-7 hours, filtering, and drying to obtain a boron nitride-silicon polymer composite material;
[0011] Step 2: Take polyimide, aluminum oxide powder, boron nitride-silicon polymer composite material, add deionized water, dispersant, thickener, wetting agent, epoxy acrylate, stir evenly, and obtain a water-based adhesive.
[0012] More optimally, the preparation method of the modified boron nitride is: take cobalt acetate and deionized water, stir evenly, add the pretreated boron nitride, ultrasonically disperse for 40-60 minutes, then stir for 22-24 hours, filter, wash and dry to obtain modified boron nitride.
[0013] More optimally, the preparation method of the pretreated boron nitride is: take boron nitride and ethanol, ultrasonically disperse, add benzoin dimethyl ether, stir for 10-15 minutes, add thioglycolic acid, stir for 10-20 minutes under the action of ultraviolet light, centrifuge, wash, and dry to obtain the pretreated boron nitride.
[0014] More optimally, the preparation method of the silicon polymer is: take sodium hydroxide and deionized water, stir evenly, then add silicon dioxide, stir for 3-4 hours, add sodium chloride, tetrahydrofuran, hydrochloric acid, react for 20-40 minutes, filter, and dry to obtain silicon polymer.
[0015] More optimally, the dispersant is ammonium polyacrylate; the wetting agent is a silanol nonionic surfactant; and the thickener is sodium hydroxymethyl cellulose.
[0016] A method for preparing a lithium battery separator comprises the following steps: coating the coating slurry described in any one of claims 2 to 7 onto both sides of a polyethylene-based film, drying, and rolling up to obtain a lithium battery separator.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention uses epoxy acrylate as a bonding material, adds polyimide, aluminum oxide powder, boron nitride-silicon polymer composite material, dispersant, thickener, wetting agent, and then uses deionized water as solvent to prepare a coating slurry with good heat resistance.
[0019] Boron nitride has excellent high temperature resistance and can work stably for a long time in a high temperature environment. Boron nitride is pretreated with thioacetic acid, and then cobalt acetate is added for further reaction to prepare boron nitride with cobalt on the surface. The cobalt loading improves the heat resistance of boron nitride, thereby improving the heat resistance of the coating slurry.
[0020] 2. Use silicone polymer to compound modified boron nitride with it. The silicone polymer surface has abundant hydroxyl groups that can react with the epoxy groups on epoxy acrylate, thereby improving the dispersibility of modified boron nitride in the adhesive, solving the agglomeration problem of unmodified boron nitride, and further improving the heat resistance of the coating slurry. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The purchasers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include:
[0023] Bisphenol A type epoxy resin: model: E-51; alumina powder: particle size is 1-2μm; polyimide powder: can be purchased from Evonik of Germany, model: P84; dispersant is ammonium polyacrylate: can be purchased from Solpro Solewend of the Netherlands, model: AN33; wetting agent is silanol non-ionic surfactant: can be purchased from Dongguan Gaosijin Fine Chemical Co., Ltd., model: GSK-588; silicon dioxide: particle size is 60-80μm; COPNA resin, can be purchased from Wuhan Baohua Petrochemical New Materials Development Co., Ltd., model: FJSZ.
[0024] Embodiment 1: A water-based adhesive and a lithium battery separator using the water-based adhesive, comprising the following steps:
[0025] Step 1: Preparation of modified boron nitride:
[0026] Take 2g of boron nitride and 100mL of ethanol, disperse by ultrasonication, add 0.1g of benzoin dimethyl ether, stir for 12min, add 5g of thioglycolic acid, stir for 15min under the action of ultraviolet light, centrifuge, wash and dry to obtain pretreated boron nitride;
[0027] Take 8g of cobalt acetate and 100mL of deionized water, stir evenly, add 2g of pretreated boron nitride, ultrasonically disperse for 50min, then stir for 23h, filter, wash and dry to obtain modified boron nitride;
[0028] Step 2: Preparation of silica polymer:
[0029] Take 0.1g sodium hydroxide and 70mL deionized water, stir evenly, then add 3.2g silicon dioxide, stir for 3.5h, add 35g sodium chloride, 180mL tetrahydrofuran, 60mL hydrochloric acid, react for 30min, filter and dry to obtain silicon polymer;
[0030] Step 3: Preparation of Boron Nitride-Silicon Polymer Composite Material:
[0031] Take modified boron nitride and deionized water, and perform ultrasonic dispersion to obtain a modified boron nitride solution with a concentration of 0.2 mg / mL; take silicon polymer and deionized water, and perform ultrasonic dispersion to obtain a silicon polymer solution with a concentration of 2 mg / mL; add 100 mL of silicon polymer solution to 100 mL of modified boron nitride solution, react at 62° C. for 6 hours, filter, and dry to obtain a boron nitride-silicon polymer composite material;
[0032] Step 4: Preparation of epoxy acrylate:
[0033] Take 5g of acrylic acid, 0.4g of tetrabutylammonium bromide, and 0.03g of p-hydroxyanisole, stir evenly to obtain a mixture A; take 150g of bisphenol A epoxy resin E-51 and 0.45g of tetrabutylammonium bromide, heat to 100°C, stir evenly, add 5.2g of pentaerythritol, condense and reflux for 2.5h, cool to 82°C, add the mixture A, react for 4h, cool, and obtain epoxy acrylate;
[0034] Step 5: Preparation of coating slurry:
[0035] Take polyimide, aluminum oxide powder, boron nitride-silicon polymer composite material, add deionized water, dispersant, thickener, wetting agent, epoxy acrylate, stir evenly to obtain coating slurry;
[0036] The coating slurry comprises the following components, calculated by weight: 32 parts of polyimide, 455 parts of aluminum oxide powder, 22 parts of boron nitride-silicon polymer composite material, 1030 parts of deionized water, 21 parts of dispersant, 2.5 parts of thickener, 2.4 parts of wetting agent, and 57 parts of epoxy acrylate;
[0037] Step 6: Preparation of lithium battery separator:
[0038] The coating slurry was coated on both sides of a lithium battery polyethylene-based film with a thickness of 9 μm. The coating thickness on one side was the same, and the coating thickness on one side was 3 μm. It was dried at 66° C. to obtain a lithium battery separator.
[0039] Embodiment 2: A water-based adhesive and a lithium battery separator using the water-based adhesive, comprising the following steps:
[0040] Step 1: Preparation of modified boron nitride:
[0041] Take 2g of boron nitride and 100mL of ethanol, disperse by ultrasonication, add 0.1g of benzoin dimethyl ether, stir for 10min, add 5g of thioglycolic acid, stir for 10min under the action of ultraviolet light, centrifuge, wash and dry to obtain pretreated boron nitride;
[0042] Take 8g of cobalt acetate and 100mL of deionized water, stir evenly, add 2g of pretreated boron nitride, ultrasonically disperse for 40min, then stir for 22h, filter, wash and dry to obtain modified boron nitride;
[0043] Step 2: Preparation of silica polymer:
[0044] Take 0.1g sodium hydroxide and 70mL deionized water, stir evenly, then add 3.2g silicon dioxide, stir for 3h, add 35g sodium chloride, 180mL tetrahydrofuran, 60mL hydrochloric acid, react for 20min, filter and dry to obtain silicon polymer;
[0045] Step 3: Preparation of Boron Nitride-Silicon Polymer Composite Material:
[0046] Take modified boron nitride and deionized water, and disperse them by ultrasonic method to obtain a modified boron nitride solution with a concentration of 0.2 mg / mL; take silicon polymer and deionized water, and disperse them by ultrasonic method to obtain a silicon polymer solution with a concentration of 2 mg / mL; add 100 mL of silicon polymer solution to 100 mL of modified boron nitride solution, react at 60° C. for 5 hours, filter and dry to obtain a boron nitride-silicon polymer composite material;
[0047] Step 4: Preparation of epoxy acrylate:
[0048] Take 5g of acrylic acid, 0.4g of tetrabutylammonium bromide, and 0.03g of p-hydroxyanisole, stir evenly to obtain a mixture A; take 150g of bisphenol A epoxy resin E-51 and 0.45g of tetrabutylammonium bromide, heat to 100°C, stir evenly, add 5.2g of pentaerythritol, condense and reflux for 2h, cool to 80°C, add the mixture A, react for 3h, cool, and obtain epoxy acrylate;
[0049] Step 5: Preparation of coating slurry:
[0050] Take polyimide, aluminum oxide powder, boron nitride-silicon polymer composite material, add deionized water, dispersant, thickener, wetting agent, epoxy acrylate, stir evenly to obtain coating slurry;
[0051] The coating slurry comprises the following components, calculated by weight: 30 parts of polyimide, 450 parts of aluminum oxide powder, 20 parts of boron nitride-silicon polymer composite material, 1000 parts of deionized water, 20 parts of dispersant, 2 parts of thickener, 2.2 parts of wetting agent, and 55 parts of epoxy acrylate;
[0052] Step 6: Preparation of lithium battery separator:
[0053] The coating slurry was coated on both sides of a lithium battery polyethylene-based film with a thickness of 9 μm. The coating thickness on one side was the same, and the coating thickness on one side was 3 μm. It was dried at 65° C. to obtain a lithium battery separator.
[0054] Embodiment 3: A water-based adhesive and a lithium battery separator using the water-based adhesive, comprising the following steps:
[0055] Step 1: Preparation of modified boron nitride:
[0056] Take 2g of boron nitride and 100mL of ethanol, disperse by ultrasonication, add 0.1g of benzoin dimethyl ether, stir for 15min, add 5g of thioglycolic acid, stir for 20min under the action of ultraviolet light, centrifuge, wash and dry to obtain pretreated boron nitride;
[0057] Take 8g of cobalt acetate and 100mL of deionized water, stir evenly, add 2g of pretreated boron nitride, ultrasonically disperse for 60min, then stir for 24h, filter, wash and dry to obtain modified boron nitride;
[0058] Step 2: Preparation of silica polymer:
[0059] Take 0.1g sodium hydroxide and 70mL deionized water, stir evenly, then add 3.2g silicon dioxide, stir for 4h, add 35g sodium chloride, 180mL tetrahydrofuran, 60mL hydrochloric acid, react for 40min, filter and dry to obtain silicon polymer;
[0060] Step 3: Preparation of Boron Nitride-Silicon Polymer Composite Material:
[0061] Take modified boron nitride and deionized water, and perform ultrasonic dispersion to obtain a modified boron nitride solution with a concentration of 0.2 mg / mL; take silicon polymer and deionized water, and perform ultrasonic dispersion to obtain a silicon polymer solution with a concentration of 2 mg / mL; add 100 mL of silicon polymer solution to 100 mL of modified boron nitride solution, react at 65° C. for 7 hours, filter, and dry to obtain a boron nitride-silicon polymer composite material;
[0062] Step 4: Preparation of epoxy acrylate:
[0063] Take 5g of acrylic acid, 0.4g of tetrabutylammonium bromide, and 0.03g of p-hydroxyanisole, stir evenly to obtain a mixture A; take 150g of bisphenol A epoxy resin E-51 and 0.45g of tetrabutylammonium bromide, heat to 100°C, stir evenly, add 5.2g of pentaerythritol, condense and reflux for 3h, cool to 85°C, add the mixture A, react for 5h, cool, and obtain epoxy acrylate;
[0064] Step 5: Preparation of coating slurry:
[0065] Take polyimide, aluminum oxide powder, boron nitride-silicon polymer composite material, add deionized water, dispersant, thickener, wetting agent, epoxy acrylate, stir evenly to obtain coating slurry;
[0066] The coating slurry comprises the following components, calculated by weight: 35 parts of polyimide, 460 parts of aluminum oxide powder, 25 parts of boron nitride-silicon polymer composite material, 1050 parts of deionized water, 22 parts of dispersant, 3 parts of thickener, 2.5 parts of wetting agent, and 60 parts of epoxy acrylate;
[0067] Step 6: Preparation of lithium battery separator:
[0068] The coating slurry was coated on both sides of a lithium battery polyethylene-based film with a thickness of 9 μm. The coating thickness on one side was the same, and the coating thickness on one side was 3 μm. It was dried at 70° C. to obtain a lithium battery separator.
[0069] Comparative Example 1: The silicon polymer is not compounded with the modified boron nitride, and the rest is the same as Example 1:
[0070] A water-based adhesive and a lithium battery separator using the water-based adhesive, comprising the following steps:
[0071] Step 1: Preparation of modified boron nitride:
[0072] Take 2g of boron nitride and 100mL of ethanol, disperse by ultrasonication, add 0.1g of benzoin dimethyl ether, stir for 12min, add 5g of thioglycolic acid, stir for 15min under the action of ultraviolet light, centrifuge, wash and dry to obtain pretreated boron nitride;
[0073] Take 8g of cobalt acetate and 100mL of deionized water, stir evenly, add 2g of pretreated boron nitride, ultrasonically disperse for 50min, then stir for 23h, filter, wash and dry to obtain modified boron nitride;
[0074] Step 2: Preparation of silica polymer:
[0075] Take 0.1g sodium hydroxide and 70mL deionized water, stir evenly, then add 3.2g silicon dioxide, stir for 3.5h, add 35g sodium chloride, 180mL tetrahydrofuran, 60mL hydrochloric acid, react for 30min, filter and dry to obtain silicon polymer;
[0076] Step 3: Preparation of epoxy acrylate:
[0077] Take 5g of acrylic acid, 0.4g of tetrabutylammonium bromide, and 0.03g of p-hydroxyanisole, stir evenly to obtain a mixture A; take 150g of bisphenol A epoxy resin E-51 and 0.45g of tetrabutylammonium bromide, heat to 100°C, stir evenly, add 5.2g of pentaerythritol, condense and reflux for 2.5h, cool to 82°C, add the mixture A, react for 4h, cool, and obtain epoxy acrylate;
[0078] Step 4: Preparation of coating slurry:
[0079] Take polyimide, aluminum oxide powder, modified boron nitride, and silicon polymer, add deionized water, dispersant, thickener, wetting agent, and epoxy acrylate, stir evenly, and obtain a coating slurry;
[0080] The coating slurry includes the following components, calculated by weight: 32 parts of polyimide, 455 parts of aluminum oxide powder, 12 parts of modified boron nitride, 10 parts of silicon polymer, 1030 parts of deionized water, 21 parts of dispersant, 2.5 parts of thickener, 2.4 parts of wetting agent, and 57 parts of epoxy acrylate;
[0081] Step 5: Preparation of lithium battery separator:
[0082] The coating slurry was coated on both sides of a lithium battery polyethylene-based film with a thickness of 9 μm. The coating thickness on one side was the same, and the coating thickness on one side was 3 μm. It was dried at 66° C. to obtain a lithium battery separator.
[0083] Comparative Example 2: Cobalt is not loaded on the surface of boron nitride, and the rest is the same as Example 1:
[0084] A water-based adhesive and a lithium battery separator using the water-based adhesive, comprising the following steps:
[0085] Step 1: Preparation of silica polymer:
[0086] Take 0.1g sodium hydroxide and 70mL deionized water, stir evenly, then add 3.2g silicon dioxide, stir for 3.5h, add 35g sodium chloride, 180mL tetrahydrofuran, 60mL hydrochloric acid, react for 30min, filter and dry to obtain silicon polymer;
[0087] Step 2: Preparation of boron nitride-silicon polymer composite material:
[0088] Boron nitride and deionized water are ultrasonically dispersed to obtain a boron nitride solution with a concentration of 0.2 mg / mL; silicon polymer and deionized water are ultrasonically dispersed to obtain a silicon polymer solution with a concentration of 2 mg / mL; 100 mL of the silicon polymer solution is added to 100 mL of the boron nitride solution, reacted at 62° C. for 6 hours, filtered and dried to obtain a boron nitride-silicon polymer composite material;
[0089] Step 3: Preparation of epoxy acrylate:
[0090] Take 5g of acrylic acid, 0.4g of tetrabutylammonium bromide, and 0.03g of p-hydroxyanisole, stir evenly to obtain a mixture A; take 150g of bisphenol A epoxy resin E-51 and 0.45g of tetrabutylammonium bromide, heat to 100°C, stir evenly, add 5.2g of pentaerythritol, condense and reflux for 2.5h, cool to 82°C, add the mixture A, react for 4h, cool, and obtain epoxy acrylate;
[0091] Step 4: Preparation of coating slurry:
[0092] Take polyimide, aluminum oxide powder, boron nitride-silicon polymer composite material, add deionized water, dispersant, thickener, wetting agent, epoxy acrylate, stir evenly to obtain coating slurry;
[0093] The coating slurry comprises the following components, calculated by weight: 32 parts of polyimide, 455 parts of aluminum oxide powder, 22 parts of boron nitride-silicon polymer composite material, 1030 parts of deionized water, 21 parts of dispersant, 2.5 parts of thickener, 2.4 parts of wetting agent, and 57 parts of epoxy acrylate;
[0094] Step 5: Preparation of lithium battery separator:
[0095] The coating slurry was coated on both sides of a lithium battery polyethylene-based film with a thickness of 9 μm. The coating thickness on one side was the same, and the coating thickness on one side was 3 μm. It was dried at 66° C. to obtain a lithium battery separator.
[0096] Comparative Example 3: COPNA resin was used instead of epoxy acrylate, and the rest was the same as Example 1:
[0097] A water-based adhesive and a lithium battery separator using the water-based adhesive, comprising the following steps:
[0098] Step 1: Preparation of modified boron nitride:
[0099] Take 2g of boron nitride and 100mL of ethanol, disperse by ultrasonication, add 0.1g of benzoin dimethyl ether, stir for 12min, add 5g of thioglycolic acid, stir for 15min under the action of ultraviolet light, centrifuge, wash and dry to obtain pretreated boron nitride;
[0100] Take 8g of cobalt acetate and 100mL of deionized water, stir evenly, add 2g of pretreated boron nitride, ultrasonically disperse for 50min, then stir for 23h, filter, wash and dry to obtain modified boron nitride;
[0101] Step 2: Preparation of silica polymer:
[0102] Take 0.1g sodium hydroxide and 70mL deionized water, stir evenly, then add 3.2g silicon dioxide, stir for 3.5h, add 35g sodium chloride, 180mL tetrahydrofuran, 60mL hydrochloric acid, react for 30min, filter and dry to obtain silicon polymer;
[0103] Step 3: Preparation of Boron Nitride-Silicon Polymer Composite Material:
[0104] Take modified boron nitride and deionized water, and perform ultrasonic dispersion to obtain a modified boron nitride solution with a concentration of 0.2 mg / mL; take silicon polymer and deionized water, and perform ultrasonic dispersion to obtain a silicon polymer solution with a concentration of 2 mg / mL; add 100 mL of silicon polymer solution to 100 mL of modified boron nitride solution, react at 62° C. for 6 hours, filter, and dry to obtain a boron nitride-silicon polymer composite material;
[0105] Step 4: Preparation of coating slurry:
[0106] Take polyimide, aluminum oxide powder, boron nitride-silicon polymer composite material, add deionized water, dispersant, thickener, wetting agent, COPNA resin, stir evenly to obtain coating slurry;
[0107] The coating slurry includes the following components, by weight: 32 parts of polyimide, 455 parts of aluminum oxide powder, 22 parts of boron nitride-silicon polymer composite material, 1030 parts of deionized water, 21 parts of dispersant, 2.5 parts of thickener, 2.4 parts of wetting agent, and 57 parts of COPNA resin;
[0108] Step 5: Preparation of lithium battery separator:
[0109] The coating slurry was coated on both sides of a lithium battery polyethylene-based film with a thickness of 9 μm. The coating thickness on one side was the same, and the coating thickness on one side was 3 μm. It was dried at 66° C. to obtain a lithium battery separator.
[0110] experiment:
[0111] The performance of the lithium battery separators prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the needle puncture strength and thermal shrinkage of the lithium battery separators were tested with reference to GB / T36363-2018. The data obtained are as follows:
[0112]
[0113] Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, the silicon polymer is not compounded with the modified boron nitride, the dispersibility of boron nitride in the adhesive is poor, it is easy to agglomerate, the puncture strength of the lithium battery separator decreases, the mechanical properties decrease, the heat resistance deteriorates, and the thermal shrinkage increases. At this time, the puncture strength is only 552N, the heat resistance is poor, the longitudinal thermal shrinkage of the lithium battery separator is 1.8%, and the transverse thermal shrinkage is 1.5%. Comparative Example 2 does not load cobalt on the surface of boron nitride, the heat resistance of boron nitride deteriorates, the heat resistance of the coating slurry decreases, and the lithium battery separator is also affected. Comparative Example 3 uses COPNA resin instead of epoxy acrylate. At this time, the dispersibility of the boron nitride-silicon polymer composite material in the adhesive is poor, it is easy to agglomerate, the puncture strength of the lithium battery separator decreases, the mechanical properties decrease, the heat resistance deteriorates, and the thermal shrinkage increases. At this time, the puncture strength of the lithium battery separator is only 555N, the heat resistance is poor, the longitudinal thermal shrinkage of the lithium battery separator is 1.6%, and the transverse thermal shrinkage is 1.3%. Embodiments 1 to 3 of the present invention use epoxy acrylate as a bonding material, and a coating slurry with good heat resistance is prepared by adding polyimide, aluminum oxide powder, boron nitride-silicon polymer composite material, dispersant, thickener, wetting agent, and then using deionized water as solvent. Boron nitride has excellent high temperature resistance and can work stably for a long time under high temperature environment. Boron nitride is pretreated with thioglycolic acid, and then cobalt acetate is added to further react to prepare boron nitride with cobalt on the surface. The cobalt load improves the heat resistance of boron nitride, thereby improving the heat resistance of the coating slurry. Modified boron nitride is compounded with silicon polymer, and the silicon polymer surface has abundant hydroxyl groups that can react with the epoxy groups on epoxy acrylate, thereby improving the dispersibility of modified boron nitride in the adhesive, solving the agglomeration problem of unmodified boron nitride, and further improving the heat resistance of the coating slurry. The coating slurry prepared according to the scheme provided by the present invention has good heat resistance, and the lithium battery separator prepared therefrom has good mechanical properties and excellent heat resistance. The lithium battery separator has a needle puncture strength of up to 570N and good heat resistance. Its longitudinal heat shrinkage can reach 0.9% and its transverse heat shrinkage can reach 0.7%.
[0114] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A water-based adhesive, characterized in that: The water-based adhesive is epoxy acrylate, and the preparation method of the epoxy acrylate is as follows: take acrylic acid, tetrabutylammonium bromide, and p-hydroxyanisole, stir evenly to obtain a mixture A; take bisphenol A epoxy resin and tetrabutylammonium bromide, heat to 100° C., stir evenly, add pentaerythritol, condense and reflux for 2-3 hours, cool to 80-85° C., add the mixture A, react for 3-5 hours, cool, and obtain epoxy acrylate.
2. A coating slurry, characterized in that: The coating slurry comprises the epoxy acrylate according to claim 1, wherein the coating slurry comprises the following components, calculated by weight: 30-35 parts of polyimide, 450-460 parts of aluminum oxide powder, 20-25 parts of boron nitride-silicon polymer composite material, 1000-1050 parts of deionized water, 20-22 parts of dispersant, 2-3 parts of thickener, 2.2-2.5 parts of wetting agent, and 55-60 parts of epoxy acrylate.
3. A method for preparing a coating slurry, characterized in that: The method for preparing the coating slurry comprises the following steps: Step 1: taking modified boron nitride and deionized water, and ultrasonically dispersing them to obtain a modified boron nitride solution; taking silicon polymer and deionized water, and ultrasonically dispersing them to obtain a silicon polymer solution; adding the silicon polymer solution to the modified boron nitride solution, reacting at 60-65° C. for 5-7 hours, filtering, and drying to obtain a boron nitride-silicon polymer composite material; Step 2: Take polyimide, aluminum oxide powder, boron nitride-silicon polymer composite material, add deionized water, dispersant, thickener, wetting agent, and the epoxy acrylate according to claim 1, stir evenly, and obtain a water-based adhesive.
4. A coating slurry according to claim 3, characterized in that: The preparation method of the modified boron nitride is as follows: cobalt acetate and deionized water are taken, stirred evenly, the pretreated boron nitride is added, ultrasonically dispersed for 40-60 minutes, then stirred for 22-24 hours, filtered, washed, and dried to obtain the modified boron nitride.
5. A coating slurry according to claim 4, characterized in that: The preparation method of the pretreated boron nitride is as follows: taking boron nitride and ethanol, ultrasonically dispersing, adding benzoin dimethyl ether, stirring for 10-15 minutes, adding thioglycolic acid, stirring for 10-20 minutes under the action of ultraviolet light, centrifuging, washing, and drying to obtain the pretreated boron nitride.
6. A coating slurry according to claim 3, characterized in that: The preparation method of the silicon polymer is: take sodium hydroxide and deionized water, stir evenly, then add silicon dioxide, stir for 3-4 hours, add sodium chloride, tetrahydrofuran and hydrochloric acid, react for 20-40 minutes, filter and dry to obtain the silicon polymer.
7. A coating slurry according to claim 3, characterized in that: The dispersant is ammonium polyacrylate; the wetting agent is a silanol nonionic surfactant; and the thickener is sodium hydroxymethyl cellulose.
8. A method for preparing a lithium battery separator, characterized in that: The following steps are involved: The coating slurry according to claim 2 is applied to both sides of the polyethylene base film, dried and rolled up to obtain a lithium battery separator.
Citation Information
Patent Citations
Epoxy acrylate for UV (ultraviolet) curable coating and preparation method of epoxy acrylate
CN102558570A
Low-viscosity epoxy acrylate paint for inner wall of food can and preparation method thereof
CN103254739A
Synthesis method of modified bisphenol A epoxy acrylate
CN103450446A
Planar sealing anaerobic adhesive and preparation method thereof
CN105176420A
Manufacture method and applications of high temperature resistant and deformation resistant composite microporous membrane
CN105713228A